Arbeit am Gottesbegriff Band 3 Theologie als sprachliches Denken - Ringleben, Joachim (Universitätsverlag Göttingen, 2021)
Joachim Ringleben systematically explores the traces of linguistic thought in partly unprinted works: first in biblical contexts (prophetic speech, Ps 119, Paul), then in dogmatics (concept, Christological dogma, h. Scripture) and finally in the history of theology and philosophy (in Augustin, Hegel (Lord's Supper, St. John's Prologue, speculative logic), Kierkegaard (love of neighbor) and Jaspers (doctrine of ciphers). Translated with www.DeepL.com/Translator (free version)